POLA PEMASARAN SAPI POTONG DI PULAU MADURA - A. Yudi Heryadi (University of Jember, 2011)
The role of marketing is very important in agricultural development, including the marketing of beef cattle. Madura Island as a cattle barn in East Java greatly contributes to the need fulfillment of beef which reaches 24% of the whole supply in East Java, while East Java itself supplies the national beef needs by 23.5%.However, on one hand, breeders as beef cattle producers are in a weak position; they act only as price takers due to their low bargaining position. This research was aimed at identifying the marketing channels and institutions involved in beef cattle trading system and margin distribution of trading system of beef cattle and the marketing efficiency of beef cattle in Madura Island. The materials in this study were 30 cattle-farmers, 15 handlers, 10 itinerant traders, 10 small traders, 6 medium-scale traders, 3 large-scale traders, 5 butchers at Keppo Market of Pamekasan Regency, Bangkal Market of Sumenep Regency and Sampang Market of Sampang Regency. Sampling of farmers used accidental sampling while for other marketing agencies applied snowball sampling technique. Beef cattle marketing channel in Madura Island was very long and complex, but none of the agencies in the trade management acted as a counterweight. The amount of sales margin was determined by the size of the costs and risks carried by the selling agencies while the cost share and profit share were distributed fairly evenly, except cost share for small sellers, so that the marketing of beef cattle in Madura Island can be said efficient.Key Words: Beef cattle, marketing, margin, trading system